Analisis Kadar Asam Asetat dan Alkohol pada Ecoenzyme dari Bahan Kulit Jeruk, Mangga dan Pepaya - Liswatun Khasanah, Nurul; Nur Ilmiah, Sitti; Fitriatul Wahidah, Fita (Jurnal Matematika dan Sains (JMS), 2024)
Acetic Acid is an organic compound that is also widely applied in the health and industrial fields. Acetic acid has various functions, namely inhibiting weed growth and as a regulator of acidity in the food industry. Alcohol is a colorless and volatile liquid produced by fermentation which can be used as an antiseptic agent, wound cleanser and industry. Acetic acid and alcohol can be obtained from the fermentation process of fruit peel waste into an ecoenzyme solution. The aim of this study was to analyze the ratio of acetic acid levels and alcohol content in ecoenzymes from organic peels of oranges, mangoes and papayas. This type of research is descriptive quantitative. This research consisted of three stages, namely making ecoenzymes from orange peels (p1), mango (p2), and papaya (p3) (for 3 months). The levels of acetic acid and alcohol were determined using the acid-base titration method. The results of this study showed that the highest ecoenzyme acetic acid content was in the 3rd month of fermentation in orange peel samples on average of 3.7% and the lowest overall was 1% while the highest alcohol content was in orange peel samples on average of 0.78 % and the lowest overall is 0.18%